PENGARUH PENGGUNAAN MODEL ROLE PLAY MATERI MITIGASI BENCANA ALAM TERHADAP HASIL BELAJAR GEOGRAFI DI SMA NEGERI 6 PADANG - Suci Mardatillah; Ernawati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Geography learning in senior high schools is still dominated by conventional teacher-centered approaches, which result in low student participation and poor learning outcomes, especially in disaster mitigation topics. This study aims to examine the effect of the role play cooperative learning model on students’ Geography learning outcomes at SMA Negeri 6 Padang. This research employed an experimental method using a non-equivalent control group design. The research subjects consisted of 73 students, with class E2 as the experimental group (37 students) and class E3 as the control group (36 students). Data were collected through validated and reliable learning outcome tests, and analyzed using SPSS version 23. The study was conducted during the second semester of the 2026 academic year. The results indicated that students in the experimental class achieved higher learning outcomes than those in the control class, with an average score of 78.5. These findings suggest that the role play model effectively enhances students’ active participation and deepens their understanding of disaster mitigation concepts. In conclusion, the role play learning model has a positive and significant effect on students’ Geography learning outcomes. The implication of this study is that the role play model can be used as an effective alternative teaching strategy to improve the quality of Geography learning, particularly in disaster mitigation materials.